Green chromatography as a novel alternative for the quality control of Serjania marginata Casar. Leaves - Zanatta, Ana C. [UNESP]; S. Borges, Maiara [UNESP]; Mannochio-Russo, Helena [UNESP]; Heredia-Vieira, Silvia Cristina; Campaner dos Santos, Lourdes [UNESP]; Rinaldo, Daniel [UNESP]; Vilegas, Wagner [UNESP] (Elsevier, 2022)
In the quest for efficient sustainable alternative techniques for the quality control of medicinal plants, the present work sought to develop a green chromatographic method for the fingerprinting and standardization of the extract of Serjania marginata leaf – plant species used in folk medicine for the treatment of stomach ache. The analytical method was developed using the HPLC-PDA technique with only ethanol and water as solvents and based on the application of fractional factorial planning for the screening of variables and Doehlert matrix for the optimization procedure. The proposed green chromatographic method was compared with the HPLC method reported in the literature using the following metrics and taking into account the chromatographic performance and environmental impact of the methods: Green Chromatographic Fingerprinting Response (GCFR), HPLC-EAT (EAT – Environmental Assessment Tool), Analytical GREEnness (AGREE) and Green Analytical Procedure Index (GAPI). The green chromatographic technique was validated through the analysis of the following parameters: selectivity, linearity, detection and quantification limits, precision and robustness, while the standardization of the extract was performed through the quantification of protocatechuic acid, (+)-catechin, (–)-epicatechin, and apigenin derivatives. The optimum conditions for the application of the proposed chromatographic method were as follows: linear gradient from 10 to 55% of ethanol in 35 min, temperature of 60 °C, flow rate of 1.11 mL min−1, and phenyl hexyl column. Under these conditions, a desirability value of 0.93866 was obtained with maximum responses of 25.327 and 12.189, for peak number and GCFR, respectively. In addition, the analysis of the plant extract by HPLC-MS/MS, under the same optimized method, allowed the annotation of 21 phenolic compounds, including a phenolic acid, proanthocyanidins and flavonoids derived from quercetin, apigenin and luteolin. The results obtained show that the proposed method has good accuracy and robustness, apart from being environmentally friendly – once it satisfies the principles of Green Chemistry.
Keywords: Bioethanol; Design of Experiments; Green Chromatography; Metabolite Fingerprinting; Phenolic Compounds